Effects of water yam and corn starches on the interacting variables influencing the disintegration of chloroquine phosphate tablets (2010)
The individual and interaction effects of nature (X) and concentration (Y) of disintegrant and the relative density (Z) on the mechanical and release properties of chlor-oquine phosphate tablets were studied using a 23 factorial experiment design. Water yam starch (low level) and corn starch (high level) were used as disintegrants at concentrations of 5.0 and 20.0% w/w .The mechanical properties were assessed using the Crushing Strength (CS) and Friability (F) and the release properties by the Disintegration Time (DT) and dissolution time (t80). Increasing the concentration of disintegrants and the relative density of tablets resulted in increase in CS but decrease in F, DT and t80. The ranking of the individual coefficient values was Z>X>Y for CS, Z>X>Y for F and DT and Y>X>Z for t80, while that for the interaction coefficient was X-Z>Y-Z>X-Y for CS, Y-Z>X-Z>X-Y for F, Y-Z>X-Y>X-Z for DT and t80. Changing the disintegrant from corn starch to water yam starch resulted in decrease in CS, DT and t80 but increase in F. The results show considerable interaction between the variables employed and suggest that water yam could be an alternative disintegrant to corn starch particularly where with faster disintegration and release are required.